Diagnostic Utility of Podoplanin Immunohistochemistry Combined with the NanoSuit-Correlative Light and Electron Microscopy Method for Thoracic Malignant Tumors - Shin-ya Katsuragi; Yuri Sakano; Isao Ohta; Hisami Kato; Rei Ishikawa; Hirofumi Watanabe; Ryosuke Miyazaki; Katsuhiro Yoshimura; Hidetaka Yamada; Yasuhiro Sakai; Yusuke Inoue; Yusuke Takanashi; et al. (Diagnostics)
Background/Objectives: Differentiating thoracic malignant tumors, such as epithelioid malignant pleural mesothelioma (EMPM) and non-small-cell lung carcinoma (NSCLC), primarily comprising lung adenocarcinoma (LAC) and lung squamous cell carcinoma (LSCC), remains a challenge in routine pathological diagnosis. This study aimed to evaluate whether podoplanin (PDPN) immunohistochemistry combined with scanning electron microscopy (SEM) using the NanoSuit-correlative light and electron microscopy (CLEM) methods could serve as a reliable tool for distinguishing these thoracic malignancies. Methods/Results: Initially, PDPN expression was assessed by immunohistochemical analysis in 11 EMPM, 100 LAC, and 23 LSCC cases. PDPN positivity was predominantly observed in the cell membrane and was significantly more frequent in EMPM (100%) than in LAC (2%; p < 0.0001) or LSCC (43.5%; p = 0.0018). Subsequently, field emission–SEM (FE-SEM) observations of PDPN-positive sites on immunohistochemical slides, conducted using the NanoSuit-CLEM method, revealed distinctive ultrastructural features. EMPM exhibited densely packed, elongated microvilli, whereas such structures were absent in LAC and LSCC. Furthermore, analysis of thick-cut sections (20 μm) demonstrated extensive microvilli coverage characteristic of EMPM. Conclusions: These findings suggest that the combined approach of PDPN immunohistochemistry and FE-SEM observation of PDPN-positive sites, using the NanoSuit-CLEM method, constitutes an effective diagnostic strategy for enhancing the accuracy of distinguishing EMPM from NSCLCs.